Tumor Necrosis Factor–Related Apoptosis-Inducing Ligand Alters Mitochondrial Membrane Lipids - Sandra, Ferry (2005)
Tumor necrosis factor–related apoptosis-inducing ligand (TRAIL) has been shown to have selective antitumor activity. TRAIL induces ubiquitous pathways of cell death in which caspase activation is mediated either directly or via the release of apoptogenic factors from mitochondria; however, the precise components of the mitochondrial signaling pathway have not been well defined. Notably, mitochondria constitute an important target in overcoming resistance to TRAIL in many types of tumors. Bid is considered to be fundamental in engaging mitochondria during death receptor–mediated apoptosis, but this action is dependent on mitochondrial lipids. Here, we report that TRAIL signaling induces an alteration in mitochondrial membrane lipids, particularly cardiolipin. This occurs independently of caspase activation and primes mitochondrial membranes to the proapoptotic action of Bid. We unveil a link between TRAIL signaling and alteration of membrane lipid homeostasis that occurs in parallel to apical caspase activation but does not take over the mode of cell death because of the concurrent activation of caspase-8. In particular, TRAIL-induced alteration of mitochondrial lipids follows an imbalance in the cellular homeostasis of phosphatidylcholine, which results in an elevation in diacylglycerol (DAG). Elevated DAG in turn activates the δ isoform of phospholipid-dependent serine/threonine protein kinase C, which then accelerates the cleavage of caspase-8. We also show that preservation of phosphatidylcholine homeostasis by inhibition of lipid-degrading enzymes almost completely impedes the activation of pro-caspase-9 while scarcely changing the activation of caspase-8.